Impact of Customer Service Quality on Customer Satisfaction in Nepalese Insurance Companies - Bohara, Babin (Nepalese Journal of Management, 2025)
This study examines the impact of customer service quality on customer satisfaction in Nepalese insurance companies. Customer satisfaction is the dependent variable. The selected independent variables are responsiveness, empathy, security, time saving, and assurance. The primary source of data is used to assess the opinions of respondents regarding responsiveness, empathy, security, time saving, assurance, and customer satisfaction. The study is based on primary data from 120 respondents. To achieve the purpose of the study, a structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of impact of customer service quality on customer satisfaction in Nepalese insurance companies. The study showed a positive impact of responsiveness on customer satisfaction. It indicates that being able to react quickly leads to increase in customer satisfaction. Similarly, the study showed a positive impact of assurance on customer satisfaction. It indicates that higher the assurance, higher would be the customer satisfaction. Likewise, the study showed a positive impact of empathy on customer satisfaction. It indicates that the ability to emotionally understand what other people feel leads to increase in customer satisfaction. Further, the study showed a positive impact of security on customer satisfaction. It indicates that higher the security, higher would be the customer satisfaction. In addition, the study showed a positive impact of time saving on customer satisfaction. It indicates that higher the time saving, higher would be the customer satisfaction.